Development of the pineapple crops in Costa Rica and its impacts on natural and agro-urban ecosystems (Biocenosis, 2013)
Development of pineapple crops in Costa Rica and their impacts of natural and agro-urban ecosystems. In the early eighties pineapple production achieved international projection, at which time a new development model based on non-traditional exports in Costa Rica gathered strength due to new demands of the international market. From this, they entrenched a system of incentives and political and institutional framework to support the export of new products. By then the pineapple monoculture acquired an expansive character, covering large areas of land and employing high levels of agrochemicals. This caused a number of impacts on socio-economic, natural ecosystems and agro-urban systems. In Costa Rica, there have been impacts especially in the North, South and Caribbean zones and more recently has begun to spread also in the North Pacific. Some organizations have begun to venture into organic pineapple cultivation, characterized by a lesser extent in land use and the use of chemicals to a lesser extent and more controlled. This type of pineapple cultivation along with a series of measures to promote proper waste management of the fruit may help to reduce the negative effects on pineapple crops. However, because organic cultivation will not eradicate environmental problems, it would be practical to adjust production towards a diversification of activities, avoiding the typical impacts caused by any monoculture.
Keywords: Pineapple crops; Monoculture; Environmental impact; Costa Rica; Agrochemicals